A new record of the rare alpheid shrimp Coronalpheus natator from Isla Coiba, Panama, with remarks on Coronalpheus and Automate (Crustacea: Decapoda) - Poddoubtchenko, Denis; Anker, Arthur; Wehrtmann, Ingo S. (Revista de Biología Tropical, 2008)
The alpheid shrimp Coronalpheus natator Wicksten, 1999, originally described from the Galapagos Islands, is reported from waters of Isla Coiba National Park, Pacific coast of Panama. This is the first record of C. natator outside the type locality, and also the first record for near-continental waters of the eastern Pacific. The newly collected material from Panama is illustrated in detail. Relationships to some species of the closely related genus Automate De Man, 1888 are discussed. Rev. Biol. Trop. 56 (Suppl. 4): 297-304. Epub 2009 June 30.